NeuroHub: a research information environment for neuroscientists - Trefethen, A; De Roure, D; Newman, D; Wallom, D; Emptage, N; Lakhoo, R (e-Research South, 2012)
The NeuroHub project aims to develop a research information system for neuroscientists at three different partner institutions: Oxford, Reading and Southampton. Each research group has different working practices, research methodologies and user requirements, which have lead to the development of a system that supports a wide variety of tasks in the neuroscience research life cycle. In this paper, we present how these user requirements have been translated in a research information environment that supports a community of over 70 researchers using the system for day-to-day research tasks.